Polarization-driven dynamic laser speckle analysis for brain neoplasms differentiation - Vahid Abbasian; Vahideh Farzam Rad; Parisa Shamshiripour; Davoud Ahmadvand; Arash Darafsheh (Light: Advanced Manufacturing)
Early diagnosis of brain tumors is often hindered by non-specific symptoms, particularly in eloquent brain regions where open surgery for tissue sampling is unfeasible. This limitation increases the risk of misdiagnosis due to tumor heterogeneity in stereotactic biopsies. Label-free diagnostic methods, including intraoperative probes and cellular origin analysis techniques, hold promise for improving diagnostic accuracy. Polarimetry offers valuable information on the polarization properties of biomedical samples, yet it may not fully reveal specific structural characteristics. The interpretative scope of polarimetric data is sometimes constrained by the limitations of existing decomposition methods. On the other hand, dynamic laser speckle analysis (DLSA), a burgeoning technique, not only does not account for the polarimetric attributes but also is known for tracking only the temporal activity of the dynamic samples. This study bridges these gaps by synergizing conventional polarimetric imaging with DLSA for an in-depth examination of sample polarization properties. The effectiveness of our system is shown by analyzing the collection of polarimetric images of various tissue samples, utilizing a variety of adapted numerical and graphical statistical post-processing methods.